2022
DOI: 10.1007/s10681-022-03031-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cotyledon, leaf and root resistance to downy mildew in radish (Raphanus sativus L.)

Abstract: Radish downy mildew (DM) caused by the oomycete Hyaloperonospora brassicae f. sp. raphani is a serious problem in radish crop, an edible root vegetable of the Brassicaceae family. The objective of this research was to assess radish germplasm for DM resistance and to evaluate the response of different radish organs to the disease under controlled conditions. Forty-four radish accessions were inoculated at cotyledons and true-leaves with H. brassicae isolate R10, collected in cotyledons of field plants. The root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Leveraging a smartphone's camera enables researchers to conveniently and swiftly capture images, facilitating the analysis of plant traits and advancing agricultural practices [18]. For example, Coelho et al examined the resistance of different plant parts of radish to downy mildew, specifically cotyledons, leaves, and roots [19]. Results indicated that cotyledons were the most susceptible, while roots exhibited the highest resistance, with leaves displaying intermediate resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging a smartphone's camera enables researchers to conveniently and swiftly capture images, facilitating the analysis of plant traits and advancing agricultural practices [18]. For example, Coelho et al examined the resistance of different plant parts of radish to downy mildew, specifically cotyledons, leaves, and roots [19]. Results indicated that cotyledons were the most susceptible, while roots exhibited the highest resistance, with leaves displaying intermediate resistance.…”
Section: Introductionmentioning
confidence: 99%